Cui bono, benefit corporation? An experiment inspired by social enterprise legislation in Germany and the US - Sven Fischer; Sebastian J. Goerg; Hanjo Hamann (Max Planck Institute for Research on Collective Goods, 2013)
How do barely incentivized norms impact incentive-rich environments? We take social enterprise legislation as a case in point. It establishes rules on behalf of constituencies that have no institutionalized means of enforcing them. By relying primarily on managers' other-regarding concerns whilst leaving corporate incentive structures unaltered, how effective can such legislation be? This question is vital for the ongoing debate about social enterprise forms, as recently introduced in several US states and in British Columbia, Canada. We ran a laboratory experiment with a framing likened to German corporate law which traditionally includes social standards. Our results show that a stakeholder provision, as found in both Germany and the US, cannot overcome material incentives. However, even absent incentives the stakeholder norm does not foster other regarding behavior but slightly inhibits it instead. Our experiment thus illustrates the paramount importance of taking into account both incentives and framing effects when designing institutions. We tentatively discuss potential policy implications for social enterprise legislation and the stakeholder debate.
Keywords: D01; A12; M52; D03; L21; M14; 330; experiment; stakeholder value; social enterprise; benefit corporation; corporate law